Mechanism for Enhanced Absorption of a Solid Dispersion Formulation of LY2300559 Using the Artificial Stomach Duodenum Model - Polster, Christopher S; Wu, Sy-Juen; Gueorguieva, Ivelina; Sperry, David C (Molecular pharmaceutics, 2015)
An artificial stomach duodenum (ASD) model has been used to demonstrate the performance difference between two formulations of LY2300559, a low-solubility acidic developmental drug. The two formulations investigated were a conventional high-shear wet granulation (HSWG) formulation and a solid dispersion formulation. A pharmacokinetic study in humans demonstrated the enhanced performance of the solid dispersion formulation relative to the HSWG formulation. The C max and AUC of the solid dispersion was 2.6 and 1.9 times greater, respectively, compared to the HSWG formulation. In the ASD, the solid dispersion formulation performance was characterized by three main phases: (1) rapid release in the stomach, creating a supersaturated concentration of drug, (2) precipitation in the stomach, and (3) rapid redissolution of the precipitate in the duodenum to concentration levels that are supersaturated relative to crystalline drug. A series of complementary experiments were employed to describe this performance behavior mechanistically. Imaging experiments with a pH indicating dye showed that local pH gradients from meglumine in the solid dispersion formulation were responsible for creating a high initial supersaturation concentration in the stomach. Upon dissipation of meglumine, the drug precipitated in the stomach as an amorphous solid. Because the precipitated drug is in an amorphous form, it can then rapidly redissolve as it transits to the more neutral environment of the duodenum. This unexpected sequence of physical state changes gives a mechanistic explanation for the enhanced in vivo performance of the solid dispersion formulation relative to the HSWG formulation.